Impact of land use change on land degradation and hydrological response in the Mati Watershed for sustainable management - Jayantari, Made Widya; Eryani, I Gusti Agung Putu; Pawana, I Gusti Ngurah Agung; Pariartha, I Putu Gustave Suryantara (Brawijaya University, 2026)
Land-use change is one of the factors contributing to land degradation. Land degradation is characterized by a decrease in vegetation cover, leading to reduced infiltration capacity and increased surface runoff. The Mati Watershed is one of the watersheds in Bali Province that has experienced land changes with a rapid increase in built-up land from 2017 to 2024. Sentinel land cover data serve as remote sensing data that may be applied to the investigation of land transformation. The SWAT+ model is used to simulate changes in hydrological responses resulting from land-use changes. This research initiative aims to characterize the implications of land-use transformations on hydrological dynamics in the Mati watershed, thereby supporting sustainable management methodologies. The SWAT+ model encompasses two land-use scenarios from 2017 and 2014, which were examined using Sentinel land-cover data. The results show significant land use changes in the Mati Watershed, where the built-up area reached 92% of the total watershed area in 2024. This change is causing land degradation in the Mati River watershed, leading to changes in the Mati River’s flow rate. Most channels showed increases of 0.0004–0.0275 m³/s, with the most significant increase in downstream channels 18–20 (up to 0.0420 m³/s). Reduced infiltration capacity due to land-use changes leads to less rainwater absorption and increased surface runoff, increasing the risk of soil erosion and land degradation. To address this issue, sustainable management is needed, emphasizing increased groundwater recharge through low-impact development to reduce surface runoff and minimize environmental degradation in the watershed.